Young and burnt? Italian contribution to the international BurnOut Syndrome Study (BOSS) among residents in psychiatry - Ferrari, Silvia; Cuoghi, Giulia; Mattei, Giorgio; Carra, Elena; Volpe, Umberto; Jovanovic, Nikolina; Young and burnt? Italian contribution to the international BurnOut Syndrome Study (BOSS) a, Julian; Rigatelli, Marco; Galeazzi, Gian Maria; Pingani, Luca (La Medicina del Lavoro, 2015)
Background: The Burnout Syndrome (BS) is a common condition among health care professionals, yet data concerning its prevalence and associated factors among psychiatric residents are lacking. Objectives: To report the results of the Italian contribution to “BOSS”, an international multicentre research project aiming at estimating the burden of BS among residents in psychiatry, and at identifying factors contributing to its development and prevention. Methods: Cross-sectional study. The BOSS online questionnaire, which collected socio-demographic data and five psychometric tools (MBI-GS, AWLS, PHQ-9, SIBQ, BFI), was administered electronically to 180 Italian residents in psychiatry. Simple and multiple linear regressions were performed to analyse data. Results: 108 questionnaires provided data for the study (response rate: 60%). Mean age: 30.5±3.7 years. Eighty percent of the sample were female. A moderate level of BS emerged, related to work conditions, absence of major depression, satisfaction with pay or less academic activity. Only 0.9% (N=1) of the sample showed PHQ-9 scores suggestive of major depression, while lifetime suicidal ideation was admitted by 16% of residents. For the three dimensions of the MBI-GS, Italian sample scores were consistent with previously published results concerning pooled data in a French-Croatian sample, reporting moderate levels of BS. Higher workload, symptoms of depression and lower satisfaction predicted higher levels of Emotional Exhaustion and Cynicism. Conclusions: Italian residents in psychiatry showed overall moderate levels of BS, related to workload and work organization. Other alerts of psychic distress were found among participants, namely symptoms of depression, suicidal ideation and use of psychotropic medications.